Strong Relations Uzbekistan Plays an Important Role in Central Asia (US perspective) - Toshbekov, Bobur Bakhrom ugli (NAJAHA, 2022)
Henry Clark, the first US ambassador to Uzbekistan, recalled how the country spent its days with coupons and economic hardships when it was hard to boil the pot. Political scientist Ainura Akmatalieva stated, “In US policy in Central Asia, the desire to strengthen relations with Kazakhstan and Uzbekistan will prevail over regional dialogue”. It was noted that the US is focusing on Uzbekistan because of Afghanistan and stability. In this paper, I will analyze why the relationship between Uzbekistan and the United States is more robust than that of other Central Asian countries. A phenomenological approach is used in this study and is supported by a literature review based on open sources (articles, reports, news), accompanied by applying International Relations theory. In the last section, I try to conclude by recommending policies to the President of the Republic of Uzbekistan, Shavkat Mirziyoyev. In conclusion, I recommend maintaining strong and beneficial relations for both sides in many sectors. Still, neutrality should remain the basic concept of Uzbekistan when it comes to other industries, such as foreign policy, military agreements, and interference in any issues between Afghanistan and the Taliban.